Structure and microwave dielectric properties of BaAl2−2xLi2xSi2O8-2x ceramics. Issue 4 (15th February 2021) - Li, Chao; Ding, Shihua; Song, Tianxiu; Zhang, Yun; Zhu, Hui
Abstract: BaAl2-2 x Li2 x Si2 O8-2 x ( x  = 0, 0.005, 0.0075, 0.01, 0.02, 0.03) ceramics were synthesized by solid-state sintering method. Based on density functional theory, the first-principle calculations provided by the Cambridge Sequential Total Energy Package (CASTEP) software were introduced to the BaAl2 Si2 O8 (BAS) system. In an effort to confirm the site occupied by Li +, we discussed the formation energy and final energy of different positions of Li + doped BAS. The result demonstrated that Li + should substitute Al 3+ to promote the hexacelsian-to-celsian transformation with the aid of generated oxygen vacancies. The sintering behavior, crystal structure, surface appearance, and microwave dielectric properties of samples were investigated. Completely transformed celsian could be obtained when x  = 0.005–0.03, which lowered the sintering temperature from 1400 °C ( x  = 0) to 1300 °C ( x  = 0.03), as well as strikingly improved the compactness, quality factor ( Q  ×  f ) value and temperature coefficient of resonant frequency ( τ f ) of BAS ceramics. When x  = 0.1, unveiling the significant effects of Al-position ion substitution, BaAl1.98 Li0.02 Si2 O7.98 ceramic sintered at 1350 °C for 5 h exhibited a supreme Q  ×  f value of 48, 620 GHz, and the ε r and τ f values were 6.99 and -23.29 × 10 −6  °C −1, respectively.